The Pentahelix Approach to Oral-Systemic Health Integration: A Policy Framework for Academic-Primary Care Partnerships in Transitional Health Systems - Zelka Dapala; Rachmat Hidayat; Muhammad Ashraf (HM Publisher, 2025)
The historical bifurcation of dental and medical care pathways imposes a severe epidemiological burden, particularly within transitional health systems confronting a high prevalence of both non-communicable diseases and chronic periodontitis. Bridging this gap requires robust policy frameworks that extend beyond clinical interventions to involve cross-sectoral collaboration. To evaluate the structural efficacy, clinical outcomes, and policy implications of integrating oral-systemic healthcare using a Pentahelix collaborative model between primary healthcare centers and academic dentistry institutions in South Sumatra, Indonesia. A mixed-methods implementation study was conducted over eighteen months across twelve primary care centers in South Sumatra. The intervention utilized the Pentahelix model, integrating government authorities, academic dentistry faculties, health technology industries, community leaders, and local media. Quantitative data included inter-departmental referral completion rates, changes in patient glycemic control (HbA1c), and systemic inflammatory markers (C-Reactive Protein). Qualitative data assessed stakeholder engagement and interprofessional competencies. Implementation of the Pentahelix framework significantly improved medical-dental cross-referral completion rates from a baseline of twelve percent to seventy-six percent. Clinically, patients with comorbid type 2 diabetes and severe periodontitis receiving integrated care demonstrated a mean HbA1c reduction of 0.9% and a significant decrease in serum C-Reactive Protein levels following combined medical and non-surgical periodontal therapy. Furthermore, interprofessional competency scores among participating academic students and primary care staff increased significantly. In conclusion, the Pentahelix model provides a viable, highly effective policy framework for dismantling clinical silos in transitional health systems. By anchoring interprofessional clinical practice within a multi-stakeholder governance structure, health systems can achieve measurable improvements in both population health metrics and health workforce readiness.